Penyuluhan Hukum: Politik Penegakan Hukum melalui Radio Maria Indonesia - Joy Zaman Felix Saragih; Andy Tonggo Mikhael Sihombing; Sitorus, Rolib; Banke, Ricky (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2025)
Legal counseling is an effective method to enhance public legal awareness. Legal counseling through mass media, particularly radio, serves as a strategic means to reach a broad audience. The legal counseling program on corruption, conducted through Radio Maria Indonesia, is part of a community service initiative by lecturers from the Law Study Program at Universitas Pelita Harapan (UPH) Medan Campus. This initiative aims to provide the public with a comprehensive understanding of the definition, forms, and impact of alleged discrimination in law enforcement, as well as preventive measures. Through a communicative approach and accessible language, the program seeks to foster collective awareness and encourage active public participation in supporting strict law enforcement efforts. This study analyzes the effectiveness of legal counseling through radio in shaping critical attitudes and more proactive behavior among the public regarding corruption issues. The findings indicate that radio can serve as an efficient legal education tool, particularly in areas with limited access to formal education or digital technology.